2006
DOI: 10.1159/000325894
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of a Cytologic Diagnosis of Atypical Glandular Cells, Favor Endometrial Origin, in Pap Smears

Abstract: In our study population, 40% (22 of 55) of women who underwent biopsy following a diagnosis of AGC-EM had significant uterine lesions, with the majority of the lesions endometrial in origin. Patients with a diagnosis of AGC-EM, especially those > 50, should be followed closely, and endometrial sampling should be included in their initial workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…13,14 The category of "AGC of endometrial origin" in our study had a higher predictive value of abnormal histology (14 of 26 [54%] vs. 24 of 65 [37%]), but the difference was not statistically significant (p = 0.139) ( Table III). The study of Saad et al 15 revealed similar data. The "AGC of endometrial origin, favor neoplastic" category in our study had a predictive rate for abnormal histology of 100%.…”
Section: Cytologic Findingsmentioning
confidence: 58%
“…13,14 The category of "AGC of endometrial origin" in our study had a higher predictive value of abnormal histology (14 of 26 [54%] vs. 24 of 65 [37%]), but the difference was not statistically significant (p = 0.139) ( Table III). The study of Saad et al 15 revealed similar data. The "AGC of endometrial origin, favor neoplastic" category in our study had a predictive rate for abnormal histology of 100%.…”
Section: Cytologic Findingsmentioning
confidence: 58%
“…Mitotic figures are not typically seen in exfoliated cells but may be seen in directly sampled cells [3]. Benign endometrial cell HCG spontaneously shed in menstrual smears may especially show concerning degenerative chromatin changes, but the cell groups typically lack features commonly described in neoplasia [20], especially the more pronounced nuclear atypia seen at least in higher grade endometrial cancers [21]. Tubal metaplasia of the endometrium and other forms of endometrial metaplasia, also termed epithelial cytoplasmic change [22], have been much more frequently recognized in endometrial surgical pathology specimens than in cytology specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, well‐differentiated EMCa may not be correctly identified owing to lack, reduction, or altered quality of background watery diathesis 78, 101. Saad et al and Schorge et al have shown that majority of lesions with AGC‐EM interpretation on LBP are of EM origin (neoplastic and non‐neoplastic) compared to CPS 102…”
Section: Atypical Em Cellsmentioning
confidence: 99%